The Gender-Climate-Security Nexus: Conceptual Framework, CGIAR Portfolio Review, and Recommendations towards an Agenda for One CGIAR - Caroli, Giulia; Tavenner, Katie; Huyer, Sophia; Sarzana, Carolina; Belli, Anna; Elias, Marlène; Pacillo, Grazia; Läderach, Peter R.D. (2022)
This position paper provides a conceptual framework for the gender-climate-security-nexus, a CGIAR portfolio review of work related to the nexus, and recommendations towards an agenda for One CGIAR in addressing the nexus. We anticipate the paper will help inform the One CGIAR and its stakeholders towards an understanding of the connections between gender, climate, and security through case study examples of the gender dimensions of climate-related security risks, a review of the CGIAR work to date on the gender-climate-security nexus and how this work can be used to promote gender transformative goals in climate security research, policy, and programming, as well as recommendations for One CGIAR on what actions should be taken to inform future research and policy in addressing gendered climate impacts and associated threats to human security.